A tetrachloroazobenzene based macrocycle featuring with red-light regulated encapsulation for aryl dianionic guests. Issue 2 (9th January 2020) - Wei, Jie; Jin, Ting-Ting; Yang, Jiang-Xiong; Jiang, Xia-Min; Liu, Li-Juan; Zhan, Tian-Guang; Zhang, Kang-Da
Graphical abstract: Highlights: Macrocyclic molecule with red light responsiveness. Reversible photo-controlled molecular conformational changes. Red light regulated molecular encapsulation in solution. Abstract: A new photo-responsive tetracationic macrocycle was designed and synthesized by connecting two bis(imidazolium)-tetrachloro-azobenzene units with o -xylene linkers. The ability of red-light triggered photoisomerization of the incorporated tetrachloroazobenzene units has featured this macrocycle with reversible photo-triggered configurational transformation, benefiting from which the distinctive red-light regulated encapsulation behavior for aromatic dicarboxylic dianions in DMSO solution could be achieved.